An incidentally identified 15 cm cavernous hemangioma of the small intestine: Case report and literature review. (July 2021) - Kano, Takeshi; Fukai, Shota; Okamoto, Risa; Motomura, Yasuaki; Lefor, Alan Kawarai; Mizokami, Ken
Abstract: Introduction: Hemangiomas of the small intestine are rare, usually present with symptoms such as anemia, gastrointestinal bleeding or abdominal pain and are resected. We report resection of an incidentally identified cavernous hemangioma of the small intestine that did not present symptoms referable to the hemangioma. Although it was a large lesion, it was resected using laparoscopy and a mini-laparotomy. Presentation of case: A 29-year-old otherwise healthy man was referred for evaluation of ileal wall thickening found on a contrast-enhanced computed tomography scan obtained for the workup of chronic diarrhea. Double balloon enteroscopy (DBE) showed a cavernous hemangioma of the small intestine. The lesion was 15 cm and resected using laparoscopy and a mini-laparotomy to prevent future bleeding. The histopathological diagnosis was a cavernous hemangioma of the ileum. Discussion: Though there have been no reports of the asymptomatic patients of the disease, the recent spread of double balloon enteroscopy and capsule endoscopy will allow us to diagnose more asymptomatic hemangiomas like this patient. Also, this large lesion was able to be resected through a small incision due to its compressible nature. Conclusion: Future studies in asymptomatic patients of the disease may help to determine the optimal management for these patients. Even large hemangiomas are compressible, facilitating minimally invasive resection. Highlights: Hemangiomas of the small intestine are rare disease. They have always been diagnosed with symptoms such as anemia and bleeding so far. An asymptomatic hemangioma of the small intestine was incidentally identified. It was big, but laparoscopic resection was possible due to its compressible nature. To determine the optimal treatment for asymptomatic lesions is a task in the future.